2020
DOI: 10.3390/brainsci10050261
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Rhythm in Speech and Music in Adult Dyslexia

Abstract: Recent studies have suggested that musical rhythm perception ability can affect the phonological system. The most prevalent causal account for developmental dyslexia is the phonological deficit hypothesis. As rhythm is a subpart of phonology, we hypothesized that reading deficits in dyslexia are associated with rhythm processing in speech and in music. In a rhythmic grouping task, adults with diagnosed dyslexia and age-matched controls listened to speech streams with syllables alternating in intensity, duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…As argued in the review article of Reybrouck and Podlipniak [9], some of these sound features and their common preconceptual affective meanings may even reflect joint evolutionary roots of M&L that still prevail today, for example, in musical expressivity and speech prosody. Notably, a feature that was particularly central to half of all contributions is the temporal structure of M&L, i.e., the patterning of strong and weak syllables or beats that make up rhythm, meter and prosodic stress [6][7][8][10][11][12][13]15].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…As argued in the review article of Reybrouck and Podlipniak [9], some of these sound features and their common preconceptual affective meanings may even reflect joint evolutionary roots of M&L that still prevail today, for example, in musical expressivity and speech prosody. Notably, a feature that was particularly central to half of all contributions is the temporal structure of M&L, i.e., the patterning of strong and weak syllables or beats that make up rhythm, meter and prosodic stress [6][7][8][10][11][12][13]15].…”
mentioning
confidence: 99%
“…The authors argue that this pattern of deficits may arise from a basic deficiency in timekeeping mechanisms that affect rhythm perception across domains. Second, Boll-Avetisyan et al [7] used multiple regression analyses and found that musical rhythm perception abilities predicted rhythmic grouping preferences in speech in adults with and without dyslexia. Similarly, in an EEG study, Fotidzis et al [8] found that musical rhythmic skills predicted children's neural sensitivity to mismatches between the speech rhythm of a written word and an auditory rhythm.…”
mentioning
confidence: 99%
See 3 more Smart Citations